2010
DOI: 10.1177/1010539510379395
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Mental Health Care in Bangladesh, India, Japan, Mongolia, and Nepal

Abstract: Studies of pathways to MHC in Asian countries are feasible and can provide data of interest in the organization of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 22 publications
2
19
1
Order By: Relevance
“…Direct help seeking from faith healer in the current study was low at five percent. Interestingly, a similar low rate of 11% among patients with substance use disorders (as compared to 19% for other psychiatric disorders) was observed at the Indian site of the study by Hashimoto et al (12) This observation also lends support to possibility of different pathways to care among patients with different psychiatric disorder including substance use disorders.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Direct help seeking from faith healer in the current study was low at five percent. Interestingly, a similar low rate of 11% among patients with substance use disorders (as compared to 19% for other psychiatric disorders) was observed at the Indian site of the study by Hashimoto et al (12) This observation also lends support to possibility of different pathways to care among patients with different psychiatric disorder including substance use disorders.…”
Section: Discussionsupporting
confidence: 62%
“…A multi-national study (12) with one center in India also included subjects with substance use disorders (18% of sample). All these studies have been conducted among clinical populations in tertiary care teaching hospitals from India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 7% of people responded that faith healers and religious leaders were the first point of contact for people with mental illness and this has been reported earlier from India [42]. During the intervention period people’s attitudes and behaviors appeared to improve but not their scores on knowledge, and this is similar to other studies [17].…”
Section: Discussionsupporting
confidence: 82%
“…CMD were neither known as mental health conditions nor was treatment sought. However, about 5% of the participants preferred religious leaders/traditional healers, and earlier research has identified using similar services, too, in India (Hashimoto et al 2015). …”
Section: Discussionmentioning
confidence: 92%